Enhancing Nursing and Midwifery Student Learning Through the Use of QR Codes. Issue 4 (July 2016) - Downer, Terri; Oprescu, Florin; Forbes, Helen; Phillips, Nikki; McTier, Lauren; Lord, Bill; Barr, Nigel; Bright, Peter; Simbag, Vilma
Abstract : Abstract: A recent teaching and learning innovation using new technologies involves the use of quick response codes, which are read by smartphones and tablets. Integrating this technology as a teaching and learning strategy in nursing and midwifery education has been embraced by academics and students at a regional university.